PENGEMBANGAN BUKU AJAR MATA KULIAH BIOTEKNOLOGI BERBASIS KEARIFAN LOKAL DAERAH TABAGSEL - Batubara, Melvariani Syari; Lubis, Mutiara (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2022)
The research background is that learning biotechnology courses for biology teacher candidate students in order to achieve optimal results requires a carefully prepared and applicative learning media. The objectives achieved in this study were to determine the results of textbook products based on local wisdom in the Tabagsel area based on expert validation of learning media and biotechnology materials, the results of peer-to-peer trials of the Prodi Biologi UMTS, the results of individual trials, groups. small, and the field is limited. The method used in this research is included in development research. The results of this study indicate that the textbook products of Biotechnology subject matter based on local wisdom of the Tabagsel area based on the validation of learning media experts, the average percentage score is 76%, including in the